STRATEGI GURU FIKIH DALAM MENGATASI KEJENUHAN BELAJAR SISWA DI MADRASAH ALIYAH NEGERI 2 TABALONG: STRATEGI GURU FIKIH DALAM MENGATASI KEJENUHAN BELAJAR SISWA DI MADRASAH ALIYAH NEGERI 2 TABALONG - Ahmad Dzaky (IAI DARUL ULUM KANDANGAN, 2025)
Learning boredom is often an obstacle in the learning process, which has an impact on student motivation and learning outcomes. Symptoms of this boredom can be seen from the lack of student attention to the teacher's explanation, chatting and drowsiness that interfere with learning focus. Other factors such as uncomfortable classroom conditions and student non-compliance with the designated seating. Based on the statement, the formulation in this study is how the strategy of fiqh teachers in overcoming student learning boredom at Madrasah Aliyah Negeri 2 Tabalong. This study aims to describe the strategies used by fiqh teachers in overcoming student learning boredom, especially in fiqh learning. The subject in this study was one fiqh teacher at Madrasah Aliyah Negeri 2 Tabalong and the object was the strategy of fiqh teachers in overcoming student learning boredom at Madrasah Aliyah Negeri 2 Tabalong. This research is a type of field research with a qualitative approach. Data collection techniques are carried out by observation, interviews, and documentation. Data is processed through the process of data collection, data reduction, data display, and data verification. As for analyzing the data, it uses a descriptive method. While the data validity test uses triangulation. The results of this study indicate that boredom in learning is a common phenomenon experienced by students, characterized by symptoms such as drowsiness and lack of understanding of the material, which is caused by physical fatigue due to monotonous learning methods. Therefore, it is important for educators to apply varied and interactive methods to improve the learning atmosphere and student learning outcomes, so the strategy of fiqh teachers in overcoming student learning boredom at Madrasah Aliyah Negeri 2 Tabalong can be seen from: First, the teacher uses an expository strategy in the form of a lecture method. Second, Inquiry Strategy involving discussion and questions and answers. Third, Student Team Achievement Division (STAD) cooperative strategy by creating a pleasant learning atmosphere through group work.